Activated carbon adsorption of gold from cyanide-starved glycine solutions containing copper. Part 2: Kinetics - Tauetsile, P.; Oraby, Elsayed; Eksteen, Jacques (Pergamon Press, 2019)
The downstream processing of leachates arising from the dissolution of copper bearing gold ores in cyanide-starved alkaline glycine solutions is imperative for the successful implementation of the new leach system at industry level. This study investigates the behaviour of gold adsorption onto activated carbon in the presence of copper from cyanide-starved glycine solutions. The adsorption behaviour was kinetically investigated using the Fleming k,n model. The model had a high consistency with experimental data (up to 6 h) for both gold and copper as evidenced by the regression coefficient (R2) values which were close to 1. The effects of important parameters including glycine concentration, solution pH, cyanide concentration, initial gold concentration, adsorbent concentration and ionic strength of the solution were studied. The results showed that, except for initial gold and carbon concentrations, a variation of these major factors had a pronounced effect on copper adsorption and slightly affected the gold adsorption, both in terms of adsorption rate and overall recovery. It was also seen that the active carbon had a high adsorption tendency towards gold over copper. The gold and copper extraction from a cyanide-glycine solution containing 2 mg/L gold, 300 mg/L copper, pH 11, 5 g/L glycine, Cu:CN of 1:1 (123 mg/L CN) and 8 g/L carbon using lime as a pH modifier reached 99.0% and 52.8% respectively. Most copper and gold was recovered in the first 6 h. The corresponding initial adsorption rates are 1263.8 h-1for gold and 19.0 h-1for copper.